How do patients access and experience long-term care after stroke in the German healthcare system? A qualitative interview study - Christoph Heintze; Christine Holmberg; Sofia Banzhoff; Susanne Döpfmer (BMJ Open)
Objective Understanding how patients access and experience long-term care after stroke, including the kind of medical support desired, in a qualitative interview study; analysis with a question-focused approach adapted from grounded theory methodology.Setting Recruitment in primary care and physical therapy practices in the metropolitan area of Berlin, Germany.Participants 15 patients treated in general practice or physical therapy, whose last stroke occurred more than 2 years ago.Results ‘Shaping relationships’ was the core category extracted from the data as a necessary component to receive appropriate long-term care after stroke. Care is embedded in relationships that must be managed primarily by the study participants and their proxies in the German setting. Study participants used different strategies to shape care relationships. This process is helped or hindered by healthcare institutions. Compared with concepts of patient-centred care, patients play a more active role in shaping relationships. To improve long-term care for chronic diseases, this needs to be taken into account.Conclusion Shaping relationships is a composite skill that includes engaging in and sustaining relationships, finding and using information and communication. This skill is essential for adequate long-term care after stroke.